Essential University Physics: Volume 1 (4th Edition) Clone

Published by Pearson
ISBN 10: 0-134-98855-8
ISBN 13: 978-0-13498-855-9

Chapter 7 - Exercises and Problems - Page 132: 52

Answer

Please see the work below.

Work Step by Step

We know that in equilibrium position $\frac{dU}{dr}=0$ $\implies \frac{-nb}{r^{n+1}}-\frac{-a}{r^2}=0$ This can be rearranged as: $a-\frac{nb}{r^{n-1}}=0$ $\implies \frac{nb}{r^{n-1}}=a$ $r^{n-1}=\frac{nb}{a}$ $r=\sqrt[n-1] \frac{nb}{a}$ $ r = 2.82 \times 10 ^ {-10} m $
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.